Assessment of COVID-19–Related Immigration Concerns Among Latinx Immigrants in the US - Galletly, Carol L. (JAMA Netw Open, 2021)
IMPORTANCE: Despite the contentious immigration environment and disproportionate rates of COVID-19 infection among Latinx individuals in the US, immigrants’ concerns about engaging in COVID-19–related testing, treatment, and contact tracing have been largely unexplored. OBJECTIVE: To examine the proportions of Latinx immigrants who endorse statements about the potential negative immigration ramifications of seeking and using COVID-19–related testing and treatment services and engaging in contact tracing. DESIGN, SETTING, AND PARTICIPANTS: In this cross-sectional survey study, 25 COVID-19–related items were incorporated into the online Spanish-language survey of an ongoing study. Data were collected between July 15 and October 9, 2020, in Chicago, Illinois; Los Angeles, California; and Phoenix, Arizona. A nonrandom sample of 379 adult, Spanish-speaking, noncitizen Latinx immigrants (with either documented or undocumented immigration status) were sent surveys. Of those, 336 individuals (88.7% participation rate) returned surveys, and 43 individuals did not. An additional 213 individuals were screened but ineligible. Descriptive statistics were computed, and mean comparisons and bivariate correlations between sociodemographic variables, indices of immigration risk, and COVID-19–related survey items were conducted. MAIN OUTCOMES AND MEASURES: Items elicited agreement or disagreement with statements about immigrants’ access to COVID-19–related testing and treatment services and the potential immigration ramifications of using these services. Willingness to identify an undocumented person during contact tracing was also assessed. RESULTS: A total of 336 Latinx immigrants completed surveys. The mean (SD) age of participants was 39.7 (8.9) years; 210 participants (62.5%) identified as female, and 216 participants (64.3%) had undocumented immigration status. In total, 89 participants (26.5%) agreed that hospital emergency departments were the only source of COVID-19 testing or treatment for uninsured immigrants, and 106 participants (31.6%) agreed that using public testing and health care services for COVID-19 could jeopardize one’s immigration prospects. A total of 96 participants (28.6%) and 114 participants (33.9%), respectively, would not identify an undocumented household member or coworker during contact tracing. Reluctance to identify an undocumented household member or coworker was associated with having had deportation experiences (r = −0.17; 95% CI, −0.06 to 0.27; P = .003) but not with the number of years lived in the US (r = 0.07; 95% CI, −0.16 to 0.17; P = .15) or immigration status (r = 0.03; 95% CI, −0.07 to 0.13; P = .56). CONCLUSIONS AND RELEVANCE: In this cross-sectional survey study, a substantial number of immigrants endorsed statements about immigrants’ restricted access to COVID-19–related testing and treatment services and the potential negative immigration ramifications of using these services. These results suggest that programs for COVID-19–related testing, contact tracing, and vaccine administration that are designed to allay immigration concerns are needed.